APPLICATION OF NEW TYPES OF THE SEQUESTERING AGENTS TO COLOURISE COTTON WITH THE REACTIVE DYES IN HARD WATER - Bayerová, Petra; Hajdová, Zuzana; Burgert, Ladislav; Černý, Michal (My University, 2016)
In this work it was investigated the possibility of using developmental samples of sequestering agents to dyeing in hard water. To dyeing of cotton material were used reactive dyes of vinylsulphone type. The coloration was evaluated using the value of the degree of exhaustion of the dye bath and objective color measurement.
Aplikace nových typů sekvestračních prostředků při barvení bavlny reaktivními barvivy v tvrdé vodě
Keywords: sequestering agent; reactive dyes; hard water; sekvestrační prostředek; reaktivní barviva; tvrdá voda